Network connectivity between benevolent childhood experiences and uncertainty stress among Chinese university students - Pei, Yifei; Wang, Jingjing; Tang, Jie; Yan, Na; Luo, Yunjiao; Xie, Yaofei; Zhou, Qin; Zhang, Caiyi; Wang, Wei (Frontiers in Psychiatry, 2022)
Background: The purpose of this study was to explore the association between benevolent childhood experiences (BCEs) and uncertainty stress among Chinese university students by network analysis. Methods: A total of 1830 university students from three Chinese cities were recruited. Respondents' BCEs and uncertainty stress were self-reported using online questionnaire. The structure of the BCEs-uncertainty stress and related centrality indicators were examined for this sample. Results: The overall network model showed that “no ways to suit the important changes in life” was the most influential, followed by “all things are not going well”, “feel that there is nothing to do”, and “worry about the future”. And in this network, the most influential bridge symptom was “having a positive self-concept”. Limitations: First, due to the non-experimental, cross-sectional study design, causal relations between symptoms of BCEs and uncertainty stress could not be determined. Second, data were collected based on participants’ self-report, and the possibility of recall bias could not be excluded. Third, the sample were only collected from three cities of China, thus the results may not representative of all university students in China. Conclusion: The central symptoms of the BCEs-uncertainty stress network should be prioritized as targets in interventions and prevention efforts to reduce uncertainty stress among Chinese university students. Improving university students’ positive self-concept is important to alleviate the level of uncertainty stress among Chinese university students.